Enhancement of BMP-2 Induced Bone Regeneration by SDF-1α Mediated Stem Cell Recruitment - Zwingenberger, Stefan (Mary Ann Liebert, Inc., 2014)
Treatment of critical size bone defects is challenging. Recent studies showed that the cytokine stromal cell-derived factor 1 alpha (SDF-1α) has potential to improve the bone regenerative effect of low bone morphogenetic protein 2 (BMP-2) concentrations. The goal of this study was to demonstrate the combined effect of SDF-1α and BMP-2 on bone regeneration and stem cell recruitment using a critical size femoral bone defect model. A total of 72 mice were randomized to six groups. External fixators were implanted onto the right femur of each mouse and 3 mm defects were created. Depending on the group affiliation, adenovirally activated fat tissue grafts expressing SDF-1α or/and BMP-2 were implanted at the defect site. One day after operation, 1×10(6) murine mesenchymal stromal cells (MSCs), lentivirally transduced to express the gene enhanced green fluorescent protein (eGFP), firefly luciferase, and CXCR4 were injected systemically in selected groups. Migration of the injected MSCs was observed by bioluminescence imaging on days 0, 2, 4, 6, 8, 10, 12, 14, 21, 28, and 42. After 6 weeks, animals were euthanized and 80 μm CT-scans were performed. For histological investigations, hematoxylin and eosin-, tartrate-resistant acid phosphatase-, alkaline phosphatase-, and anti-eGFP-stained sections were prepared. BMP-2 and SDF-1α combined at the defect site increased bone volume (BV) (2.72 mm(3); 95% CI 1.95–3.49 mm(3)) compared with the negative control group (1.80 mm(3); 95% CI 1.56–2.04 mm(3); p<0.05). In addition, histological analysis confirmed a higher degree of bone healing in the BMP-2 and SDF-1α combined group compared with the negative control group. Bioluminescence imaging demonstrated higher numbers of migrated MSCs toward the defect site in the presence of both BMP-2 and SDF-1α at the defect site. Furthermore, eGFP-labeled migrated MSCs were found in all defect areas, when cells were injected. The ratio of osteoblasts to osteoclasts, assessed by immunohistological staining, was higher and thus showed a trend toward more bone formation for the combined use of BMP-2 and SDF-1α compared with all other groups. This study demonstrated that SDF-1α enhanced BMP-2 mediated bone healing in a critical size segmental bone defect model. Notably, both proteins alone also provided a cumulative effect on MSC attraction toward the site of injury.